BETWEEN THE LANGUAGE Of MICROSOFT AND BORGES - Sebastián Chavarría, Leonel (2010)
In 2008, the union representing education workers in Mexico, submitted for consideration the following question: “Do you think that education should be a strong link with employment and productive?”. This survey showed the following results: a resounding 92% answered yes, 1% were unsure, and only 7% said that there should be greater linkage. What is your opinion? To answer this question, if we reflect a bit, we must first be clear about the level of education referred to the term “education” in that question. If the survey relates to higher education or job training, response, in principle, I believe there should be affirmative. In general terms it is easy to see the desirability of linking students from these levels of education to the labor market to help enrich their nascent professional experience, develop certain professional skills, and thus bring them closer to the possibility of obtaining a desired job to completion of their studies. And yet, in a visionary strategy aimed at the upper layers of knowledge, it is desirable that some research institutes in our universities to become the engine of development of various productive activities, using the example of Stanford University has been largely responsible for the impressive economic and technological development in the region of Silicon Valley. However, you must understand that asks the question who is the union that is responsible for basic education in Mexico. For this reason we may assume that the term “education” in the survey, refers to the education provided in educational attainment for the primary level. Under this assumption and to clarify the level of education referred to the initial question might take the following form: Do you think that the basic and upper secondary education must have a strong link with employment and productive? . Thus, the question seems strange. How to link to underage students with labor? Obviously the idea is not logical for a direct link through labor practices. If not, does that render the survey made by the largest union in Latin America?